Pengembangan Formula Wedang Secang Sebagai Minuman Kemasan Rendah Kalori - Nutrisia A S; Indri Kusuma Dewi; Youstiana Dwi Rusita (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Wedang Sappanwood, Physical Stability, Stability of Antioxidant, Test Hedonik, Low in Calories. Wedang sappanwood is a traditional drink of Indonesia, especially from the region of Central Java, which is made from the wood of caesalpinia sappan (Sappan L caesalpia) which gives a fresh red color like wine (wine). In addition to wood, sappanwood in wedang sappanwood also there are other spices that serves as a flavor enhancer. Empirically wedang sappanwood can be efficacious for preventing and minimizing the occurrence of degenerative disease through its activity as antioxidant and lowering blood sugar so that the necessary development of other caesalpiniasappan became preparations down ready low-calorie drink that is safe for diabetics. This research aims to develop preparations Wedang Sappanwood As lowcalorie Beverages in view of physical stability, stability of antioxidant and consumer acceptance (test hedonik). Test results on hedonik parameter that gets the highest value is the color of the material, then followed its homogeneity, the aroma, viscosity, and most smaller parameter flavor. The physical test result wedang sappanwood in Weeks 0 through Sunday XII shows the results organoleptc the smell of stale spices, brown color, liquid form, there are deposits of liquid, viscosity 1 cp, and pH of 4.23. Test results on hedonik parameter that gets the highest value is the color of the material, then followed its homogeneity, the aroma, viscosity, and most small parameter flavor. Test of antioxidants in 0 to month decline to III activities antioxidant it is characterized with a price less than the CI50 150 ppm of antioxidant activities are categorized, so weak.